Fraud Hexagon Theory And Fraudulent Financial Statement In IT Industry In Asean - Tanggor Sihombing; Giena Eirene Panggulu (Universitas Muhammadiyah Malang, 2022)
This study aims to determine what factors influence fraudulent financial statements. Factor analysis of financial statement fraud uses fraud hexagon theory with financial target and external pressure variables to represent pressure, director change and CEO's education factors to represent capability, effective monitoring, and whistleblowing system factors to represent opportunity factors, total accrual ratio to represent rationalization, CEO's duality to represent ego and audit fees to represent collusion. Financial statement fraud is detected using the F-Score Model. The research sample is comapanies engaged in the information technology industry which is listed on S&P Capital IQ in the 2019-2021. Data was collected by purposive sampling method. The data processing method uses the Panel Data Regression Analysis with Fixed Effect Model (FEM). The results of the study show that financial targets have a positive effect on fraudulent financial reporting. Then, external pressure, rationalization and collusion have a negative effect on fraudulent financial statements. Meanwhile, director change, CEO's education, effective monitoring, whistleblowing system, and ego does not influence fraudulent financial statements. This research can be used as a reference for shareholders to prevent factors that can cause fraudulent financial reporting.